2003
DOI: 10.1023/b:gene.0000003656.19330.ba
|View full text |Cite
|
Sign up to set email alerts
|

Assortative Mating and Fertility in twoDrosophila subobscuraStrains with different Mitochondrial DNA Haplotypes

Abstract: The mating pattern and female fertility on the two main mitochondrial DNA haplotypes (I and II) of Drosophila subobscura were studied, in an attempt to find possible differences between them in relation to sexual selection or isolation that could explain the populational dynamics and the co-existence of these two strains in nature. The mating pattern indicated an assortative mating in population cages, where couples of the same haplotype, mainly those of haplotype I, mated more often. However, the significatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…This result could partially explain why haplotype VIII is the most frequent haplotype on some of the Canary Islands. Additionally, comparisons between haplotypes I and II did not give significative differences, contrarily to Castro et al (2003) and Christie et al (2004). These present results confirm that the fitness differences observed in these two haplotypes were surely due to cytonuclear interactions and not to direct selection upon the mtDNA.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This result could partially explain why haplotype VIII is the most frequent haplotype on some of the Canary Islands. Additionally, comparisons between haplotypes I and II did not give significative differences, contrarily to Castro et al (2003) and Christie et al (2004). These present results confirm that the fitness differences observed in these two haplotypes were surely due to cytonuclear interactions and not to direct selection upon the mtDNA.…”
Section: Discussionsupporting
confidence: 78%
“…Results indicated that natural populations have not yet reached a drift-selection equilibrium, because of periodic bottlenecks as well as some kind of selection, due to environmental heterogeneity (seasonal changes), possibly acting upon nuclear inversion polymorphism frequencies associated with mtDNA haplotypes. Many studies concerning the genetic dynamics of mtDNA in D. subobscura indicate the existence of cytonuclear interactions between the mtDNA and nuclear markers (Fos et al, 1990;García-Martínez et al, 1998;Oliver et al, 2002;Castro et al, 2003;Christie et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, males contribute with nuclear genes, which generates the nuclear variability necessary in cytonuclear relationships. In this sense, as indicated above, we also consider the mating pattern relevant, and this is an experiment that we carried out (Castro et al, 2003); in this experiment, the mating pattern indicated an assortative mating in population cages, where couples of the same haplotype …”
Section: Discussionmentioning
confidence: 99%
“…), so a direct extrapolation to nature is not possible. In fact, Castro et al (2003) found, in relation to female fertility, that the adaptation to laboratory conditions gave a more global efficiency in the production of the offspring. In this situation, we can only say that under laboratory conditions, flies with haplotype II have a higher fitness than flies with haplotype I, and, thus, haplotype II would displace haplotype I in competition experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation